New Ring-Like Models and ab Initio DFT Study of the Medium-Range Structures, Energy and Electronic Properties of GeSe2 Glass - Akalın, Elif; Holomb, R.; Mitsa, V.; AKYÜZ, SEVİM (Taylor & Francis Ltd, 4 Park Square, Milton Park, Abingdon Ox14 4Rn, Oxon, England, 2013)
Ab initio DFT calculations were performed on GenSem nanoclusters (n=2, 3, 5, 6, 12; m=6-9, 14, 16, 30) that represent the local structure of GeSe2 glass and on some defect' GenSem clusters that are thought to be related to the inhomogeneity of the structure at the nanoscale. The optimal geometries, total energies and their derivatives as well as the electronic properties of GenSem nanoclusters were calculated using traditional DFT method. In addition, the TD-DFT method has been applied to calculate the electronic band gaps of the clusters. The calculated physico-chemical properties of GenSem nanoclusters and their couplings with the local-and medium-range order structure formations in GeSe2 glass are analysed and discussed.
Keywords: Ab Initio; DFT; GeSe2 Glass; Finite Clusters; Sonlu Kümeler